The Significance of Three Pillars in Ayurveda - Gouramma R Elangadi; Shilpashree K. H. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2023)
Health is the real wealth in life, and maintaining it requires adopting the daily routine and regimen mentioned in Ayurvedic medical science. The study of Ayurveda stands fundamentally on three pillars, known as the Tridoshas: Vata, Pitta, and Kapha. Formed by combinations of the five basic elements, these doshas are directly responsible for an individual’s physical and mental well-being. Vata represents Air, Pitta represents Fire, and Kapha represents Water. A thorough understanding of these doshas plays a vital role in accurately diagnosing illnesses and successfully managing diseases through proper diet and lifestyle regimens.